STIFFNESS OF THIN-WALLED CHASSIS REINFORCED BY VERTICAL L-GUSSET PLATE UNDER BENDING AND TORSIONAL LOADS - bin Yob, Ir Dr Mohd Shukri (Journal of Mechanical Engineering and Technology (JMET), 2020)
It has been a great concern to increase the efficiency of a vehicle in the automotive industry. Typical energy breakdown of the energy consumption reveals that around 22% of the total fuel energy were used, where the rest were loss to the environment. Huge reserved of fuel can be made when a fraction of the loss can be minimized. Thin-walled chassis is one of the suggested methods in order to reduce weight of a vehicle. However, it was also debated that the beam or shell model might lose its ability to withstand forces acting on it when the critical load reach the highest point. Thus, this study intended to analyze the effect of gusset plate reinforcement on chassis towards bending and torsional load. From the study, it was found that the bending stiffness of the chassis reduced about 222.45% and increase about 84.75% for torsional stiffness. Hence, it can be concluded that gusset plate reinforcement designed and placed in this study is a good alternative to improve torsional stiffness and not the bending stiffness of thin-walled chassis.